PHARMACOTHERAPY IN MUSCLE DYSMORPHIC DISORDER: CLINICAL CONSIDERATIONS AND THE LIMITS OF EXTRAPOLATING EVIDENCE FROM BODY DYSMORPHIC DISORDER - Łęczycka, Anna; Łysak, Kinga; Haduch, Kinga; Michalska, Zuzanna; Ordyczyńska-Mardyła, Nicole Aleksandra; Stranz, Izabela Zuzanna; Stańczyk, Aleksandra; Chorąży, Olga; Strzelczyk, Joanna; Kędziora, Amelia; Suchta, Iga (International Journal of Innovative Technologies in Social Science, 2026)
Background: Muscle dysmorphic disorder is a specifier of body dysmorphic disorder (BDD) characterized by a tenacious belief of insufficient muscularity. Although currently classified within BDD, muscle dysmorphism exhibits distinct clinical and behavioral features, constituting compulsive exercise, rigid dietary practices, and use of performance-enhancing substances. Aforementioned differences raise concerns regarding applicability of pharmacotherapeutic strategies derived from BDD studies to patients with muscle dysmorphism. The aim of the study is to critically evaluate the existing literature on pharmacotherapy in body dysmorphic disorder and assess its clinical applicability to muscle dysmorphic disorder, with considerations of diverging neurobiological, phenomenological, and behavioral distinction limiting direct generalizability.Methods: A broad literature search was conducted in three major databases: PubMed, Cochrane Library, and Google Scholar, utilizing search terms (“muscle dysmorphism” or “muscle dysmorphic disorder” or “bigorexia nervosa” or “body dysmorphic disorder”) and (“pharmacotherapy” or “treatment” or “medication” or “pharmaceutical”). References were screened for relevance, and a total of 20 studies published between 1996 and 2026 were included in the analysis.Results: This review evaluates and summarizes established pharmacological strategies used in the treatment of BDD and examines their potential relevance for muscle dysmorphic disorder. Selective serotonin reuptake inhibitors (SSRIs) remain the most consistently supported pharmacological intervention, demonstrating meaningful reductions in symptom severity across several studies. Additional treatments, including clomipramine and serotonin–noradrenaline reuptake inhibitors, have shown potential benefits in selected cases. Emerging therapeutic approaches, such as glutamatergic modulators, intranasal oxytocin, and psychedelic-assisted therapy, remain experimental. However, no clinical trials have specifically examined pharmacotherapy in muscle dysmorphic disorder.Conclusions: Pharmacological strategies developed for BDD may provide partial therapeutic benefit, important differences in clinical presentation and potential neurobiological mechanisms limit direct extrapolation to muscle dysmorphic disorder. Future research should prioritize clinically controlled randomized trials exploring targeted pharmacological treatments for this condition.